Gaudiya Vaisnava Studies: Mapping the Field - Wong, Lucian (Religions of South Asia, 2015)
Gaudiya Vaisnavism, which traces its origins to the ecstatic Ben gali Krsna devotee, Krsna Caitanya (1486-1533), has indelibly shaped the socio religious landscape of Bengal and significantly impacted other regions of the Indian subcontinent, such as Orissa, Bihar, Assam, Manipur, Uttar Pradesh, and Rajasthan. The present article provides a current map of the field of the study of the Gaudiya Vaisnava tradition, from its inception to the early twentieth century, based largely on recent critical English-language scholarship. Adopting a thematic historical approach, it highlights the contextual specificity of recent scholarship and provides a heuristic framework for understanding the tradition and its historical dynamics.